PTH-273 A single surgeon's experience of retroperitoneal sarcoma excision. (22nd June 2015) - De Soyza, J; Humes, D; Collins, E; Ashford, R; Kennedy, C; McCulloch, T; Walter, C; Robinson, M
Abstract : Introduction: This study aimed to document a single surgeon's experience of surgery to excise primary retroperitoneal sarcomas. Method: Patients with retroperitoneal sarcoma referred to a surgeon at Nottingham University Hospitals via the East Midlands Sarcoma Service between 2006 and 2013 were included. Patient demographics, tumour characteristics and peri-operative events were recorded from the patients' casenotes. Results: Thirty-three patients (39% female) with a median age of 64-years (IQR 52–70) were reviewed. The median length of symptoms at presentation was 6 months (IQR 3–12). The majority of tumours were liposarcomas (64%) and leiomyosarcomas (30%). Nine tumours were Trojani grade 1; 10 were grade 2 and 14 were grade 3. Average tumour weight was 3050g (IQR 2156–9022). Macroscopic clearance (R0/R1) was achieved in 91% cases. Twenty-three cases (69%) required contiguous organ resection with nephrectomy the commonest (17 cases); followed by colectomy (7); splenectomy (6); and small intestine (5). There was no 30-day post-operative mortality. 24 (72.7%) patients experienced post-operative complications, 7 (21.2%) of which were of a Clavien-Dindo grade greater than 3. Median total length of stay in hospital was 7 (IQR 5–8.5; range 2–45) nights. Fifteen (45.5%) patients required care in an intensive therapy unit (ITU) or a high dependency unit (HDU). Median follow up was 31 months (IQR 11–50); during which 10 patients (30%) died and 11 (33%) developed recurrence. Median recurrence-free survival (excluding patients with metastasis) was 22 months (IQR 7–44). Estimated 5 year local recurrence-free survival rate was 51.9%. Estimated 5 year disease specific survival rate was 58.6%. Conclusion: Complete excision of primary retroperitoneal sarcoma frequently required resection of other organs. Reviewing our data with data from other centres, perhaps via a multidisciplinary team, may improve sarcoma management. Disclosure of interest: None Declared.